2019
DOI: 10.1088/1755-1315/337/1/012010
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment of industrial enterprises via adsorption method

Abstract: The publication justifies the feasibility of adsorption method of industrial wastewater treatment from aromatic compounds. Objects and methods of research are described. Studies of adsorption mechanisms of aromatic compounds on bentonites of various modifications made it possible to establish the most effective sorption rock clay-based materials, as well as filter compositions. Bentonite modified with carbon nanotubes after heat treatment 550 ° C proved to be the most effective with respect to the studied arom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The main type of galvanic waste is washing water containing a large amount of heavy metal ions [5]. An analysis of existing methods of treatment of natural and heavy metals wastewater has shown that one of the promising is the sorption method using natural inorganic materials as sorbents [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The main type of galvanic waste is washing water containing a large amount of heavy metal ions [5]. An analysis of existing methods of treatment of natural and heavy metals wastewater has shown that one of the promising is the sorption method using natural inorganic materials as sorbents [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…For the treatment of metal-containing wastewater, adsorption technologies are more promising and costeffective [4]. They have the following advantages: the process simplicity, speed, and suitability for wastewater with moderate and low concentrations of HMI [5].…”
Section: Introductionmentioning
confidence: 99%